Real Time Clock (RTC) Module Based Dance Humanoid Robot Timer System - Amiruddin, Nanda Fahmi; Fadlil, Abdul (Association for Scientific Computing Electrical and Engineering (ASCEE), 2023)
The Indonesian Dance Robot Contest (KRSTI) is a competition for the manufacture, design, and programming of dance robots with elements of the arts and culture of the dance department, especially the archipelago. The obstacle faced by the robot is when the robot is required to stop according to time on the music but there is a movement that appears when the time has been declared over. The method used is using the RTC module. The DS3231 type RTC module is a circuit that functions to store time and date with accuracy and precision and is integrated with the AT24c32 eeprom serial for other data storage purposes. The results of time research testing on this robot are running well, the first results obtained are that the robot can adjust the time when it runs. Furthermore, at the time of pause the RTC module does not interfere with the running of the robot. Finally, the success rate of the robot stopping at the specified time is 100%, the robot can be tested with time according to the user's wishes.